Married to the Military The Employment and Earnings of Military Wives Compared with Those of Civilian Wives - Hosek, James (RAND Corporation, 2002)
Focusing on military wives' contribution to family income, the authors find that, in contrast to civilian wives, military wives are willing to accept lower wages rather than search longer for jobs. They work less than civilian wives if they have young children but more if their children are older; are less probable to work as they get older; and respond to changes in the unemployment rate as workers with a permanent attachment to the work force, not as "added workers."